Back cover: Imaging mass spectrometry of the visual system: Advancing the molecular understanding of retina degenerations. Issue 4 (April 2016) - Bowrey, Hannah E.; Anderson, David M.; Pallitto, Patrick; Gutierrez, Danielle B.; Fan, Jie; Crouch, Rosalie K.; Schey, Kevin L.; Ablonczy, Zsolt
Abstract : DOI:10.1002/prca.201500103 Damage associated with the bisretinoid, A2E, has been implicated in blinding diseases. Imaging mass spectrometry of flat mounted retinal pigment epithelial tissue from mice, rabbits, macaques, and humans provided evidence that the distribution of A2E depends on retina and eye anatomy. These comparative data support the idea that elevated levels of A2E are indicative of reduced metabolic activity in the retina. Further details can be found in the article by Hannah E. Bowrey et al. on page 391.